Sunbelt capitalism : Phoenix and the transformation of American politics - Shermer, Elizabeth Tandy (Politics and culture in modern America., 2013)
Historian Elizabeth Tandy Shermer examines how Barry Goldwater and elite Phoenix businessmen used policy and federal funds to fashion a postwar "business climate," setting off an interstate competition for investment that transformed American politics.